2017
DOI: 10.4236/jss.2017.56001
|View full text |Cite
|
Sign up to set email alerts
|

Positive Well-Being and Work-Life Balance among UK Railway Staff

Abstract: Failure to manage the well-being and work-life balance of railway workers may result in an increased risk to train safety and employees' health. This article reports the findings of a study that measured positive well-being and work-life balance, and identified the factors affecting these among UK railway staff. On the whole, staff who perceived high levels of control and support had a better work-life balance and an increased sense of well-being. A positive personality was associated with positive well-being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
3
23
0
Order By: Relevance
“…Such stressors also have been found to affect work-life balance and positive well-being [2]. Social support and personality have been found to play buffering roles between fatigue and positive well-being [1]- [6], while job demands and shift work have been found to be associated with a high level of fatigue, negative work-life balance (also called work-life conflict) [1] [7], and impaired positive well-being [8]. Previous studies have demonstrated that fatigue is strongly re-DOI: 10.4236/jss.2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such stressors also have been found to affect work-life balance and positive well-being [2]. Social support and personality have been found to play buffering roles between fatigue and positive well-being [1]- [6], while job demands and shift work have been found to be associated with a high level of fatigue, negative work-life balance (also called work-life conflict) [1] [7], and impaired positive well-being [8]. Previous studies have demonstrated that fatigue is strongly re-DOI: 10.4236/jss.2018.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work among train crew found that job characteristics predict work-life balance and well-being (both at work and outside work) as well as occupational fatigue [1] [8]. Such job characteristics affecting both fatigue and well-being include high workload, poor job control and support, exposure to noise and vibration, and shiftwork.…”
Section: Introductionmentioning
confidence: 99%
“…Much debate surrounds the term "balance" (Frone, 2003;McMillan et al, 2011;Timms et al, 2015), which is now recognized as a distinct construct from WFC (Allen & Martin, 2017; Greenhaus & Allen, 2011). Negative outcomes, including burnout, low life satisfaction and low well-being, have been associated with difficulties maintaining satisfactory work-life balance (Fan & Smith, 2017;Greenhaus, Collins, & Shaw, 2003;Kanwar, Singh, & Kodwani, 2009). Negative outcomes, including burnout, low life satisfaction and low well-being, have been associated with difficulties maintaining satisfactory work-life balance (Fan & Smith, 2017;Greenhaus, Collins, & Shaw, 2003;Kanwar, Singh, & Kodwani, 2009).…”
Section: The Work-life Interfacementioning
confidence: 99%
“…In this paper work-life balance is considered to be individuals' overall appraisal of the extent to which their effectivenss and satisfaction in work and family roles are consistent with their life values at a specific point in time (Greenhaus & Allen, 2011). Negative outcomes, including burnout, low life satisfaction and low well-being, have been associated with difficulties maintaining satisfactory work-life balance (Fan & Smith, 2017;Greenhaus, Collins, & Shaw, 2003;Kanwar, Singh, & Kodwani, 2009).…”
Section: The Work-life Interfacementioning
confidence: 99%
“…Recent research has provided evidence of the ability for single-item measures to provide reasonably valid and reliable measures of well-being related constructs (Williams & Smith, 2012;Williams & Smith, 2013;Williams, 2015;Galvin & Smith, 2015;Williams & Smith, 2016;Nelson & Smith, 2016;Fan & Smith, 2017a;Fan & Smith, 2017b;Williams, Pendlebury, Thomas & Smith, 2017;Smith & Smith, 2017c) and for the combination of predictor measures to predict variance in well-being outcomes (Mark & Smith, 2008;Mark & Smith, 2012a;Mark & Smith, 2012b;Smith, Wadsworth, Chaplin, Allen & Mark, 2009;Capasso, Zurlo & Smith, 2016). The result was a set of measures that could be combined together to potentially provide a multi-dimensional measure of well-being and factors that could be contributing to well-being outcomes, however the exact nature of how these would be implemented in practice has not been directly established.…”
Section: The Wellbeing Process Questionnairementioning
confidence: 99%